Molecular Epidemiology of Foot-and-Mouth Disease Viruses in the Emirate of Abu Dhabi, United Arab Emirates - Yassir M. Eltahir; Hassan Zackaria Ali Ishag; Jemma Wadsworth; Hayley M. Hicks; Nick J. Knowles; Valérie Mioulet; Donald P. King; Meera Saeed Mohamed; Oum Keltoum Bensalah; Mohd Farouk Yusof; Esmat Faisal Malik Gasim; Zulaikha Mohamed Al Hammadi; et al. (Veterinary Sciences, 2024)
Foot-and-mouth disease (FMD) is an endemic disease in the United Arab Emirates (UAE) in both wild and domestic animals. Despite this, no systematic FMD outbreak investigation accompanied by molecular characterisation of FMD viruses (FMDVs) in small ruminants or cattle has been performed, and only a single report that describes sequences for FMDVs in wildlife from the Emirate has been published. In this study, FMD outbreaks that occurred in 2021 in five animal farms and one animal market in the Emirate of Abu Dhabi were investigated. Cases involved sheep, goats, and cattle, as well as Arabian oryx (Oryx leucoryx). Twelve samples were positive for FMDV via RT-qPCR, and four samples (Arabian oryx n = 1, goat n = 2, and sheep n = 1) were successfully genotyped using VP1 nucleotide sequencing. These sequences shared 88~98% identity and were classified within the serotype O, Middle East–South Asia topotype (O/ME-SA). Phylogenetic analysis revealed that the Arabian oryx isolate (UAE/2/2021) belonged to the PanAsia-2 lineage, the ANT-10 sublineage, and was closely related to the FMDVs recently detected in neighbouring countries. The FMDV isolates from goats (UAE/10/2021 and UAE/11/2021) and from sheep (UAE/14/2021) formed a monophyletic cluster within the SA-2018 lineage that contained viruses from Bangladesh, India, and Sri Lanka. This is the first study describing the circulation of the FMDV O/ME-SA/SA-2018 sublineage in the UAE. These data shed light on the epidemiology of FMD in the UAE and motivate further systematic epidemiological studies and genomic sequencing to enhance the ongoing national animal health FMD control plan.